2016
DOI: 10.1021/acs.joc.6b01599
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Asymmetric Addition of Alkyl and Aryl Alkynes to N-(Diphenylphosphinoyl)imines

Abstract: A 3,3'-di(1-diphenylmethylpiperazinyl)methyl HBINOL compound, (S)-11, was prepared from the Mannich-type reaction of (S)-HBINOL with paraformaldehyde and 1-(diphenylmethyl)piperazine. This compound can catalyze the asymmetric reaction of alkyl and aryl alkynes with N-(diphenylphosphinoyl)imines in the presence of EtZn and Ti(OPr). It exhibits unprecedented high enantioselectivity (up to 85% ee) for a simple alkyl alkyne addition to the N-(diphenylphosphinoyl)imines. The easy removal of the N-(dipehenylphosphin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Initial reports on the A 3 coupling reaction demonstrated that the reaction could be catalysed by silver [32], gold [33], and copper [34] via a one-pot synthesis. Other studies demonstrated various metals, including cadmium [35], cobalt [36], iron [37], mercury [38], indium [39], manganese [35], nickel [40], tin [35], zirconium [41], and zinc [42][43][44][45][46] facilitate the A 3 coupling. These reactions often require an inert atmosphere, high temperatures, and long reaction times.…”
Section: Trial Experiments Includementioning
confidence: 99%
See 1 more Smart Citation
“…Initial reports on the A 3 coupling reaction demonstrated that the reaction could be catalysed by silver [32], gold [33], and copper [34] via a one-pot synthesis. Other studies demonstrated various metals, including cadmium [35], cobalt [36], iron [37], mercury [38], indium [39], manganese [35], nickel [40], tin [35], zirconium [41], and zinc [42][43][44][45][46] facilitate the A 3 coupling. These reactions often require an inert atmosphere, high temperatures, and long reaction times.…”
Section: Trial Experiments Includementioning
confidence: 99%
“…A proposed transition state model hypothesised that the nitrogen atoms coordinate with Cu in a bidentate fashion while the oxygen serves as a hinge (Scheme 30). Pu employed Binol derivatives with a combination of zinc and titanium to achieve high yields and enantioselectivities [45]. Herein, Binol derivatives were designed to incorporate a dimorpholinylmethyl moiety at the 3,3 positions, facilitating chiral induction by restricting substrate entry and allowing additional coordination between the heteroatoms and the metal salt.…”
Section: Homobidentate Ligands Oo-homoligands/binolmentioning
confidence: 99%
“…Despite this, few studies have explored the potential of H 8 BINOL as a chiral uorescent probe, and the majority of research work on H 8 BINOL has focused on its use in asymmetric catalysis. [26][27][28][29][30][31][32] Despite being widely used in various elds as a catalyst for research on synthesis, the application of H 8 BINOL as a chiral self-assembly bamboo-like carbon nanotube and uorescent probe for detecting cinchonidine has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…BINOL has been widely used to synthesize chiral fluorescent probes due to its two naphthalene rings, good rigidity, and C2-axis chirality [ 11 , 12 , 13 ]. However, there are few studies based on H 8 -BINOL, which is primarily involved in asymmetric catalysis and asymmetric synthesis, and few reports of the use of H 8 -BINOL in chiral fluorescent probes [ 14 , 15 , 16 ]. H 8 -BINOL, a partially hydrogenated derivative of BINOL, due to SP3 carbon atoms hybridization, an increased volume, and an increased electron density on the aromatic ring, significantly differs from BINOL [ 17 ].…”
Section: Introductionmentioning
confidence: 99%